Promoter DNA hypermethylation of TaGli-γ-2.1 positively regulates gluten strength in bread wheat - Zhengfu Zhou; Congcong Liu; Maomao Qin; Wenxu Li; Jinna Hou; Xia Shi; Ziju Dai; Wen Yao; Baoming Tian; Zhensheng Lei; Yang Li; Zhengqing Wu (Journal of Advanced Research, 2022)
Introduction: Gliadins are the major components of gluten proteins with vital roles on properties of end-use wheat product and health-relate quality of wheat. However, the function and regulation mechanisms of γ-gliadin genes remain unclear. Objectives: Dissect the effect of DNA methylation in the promoter of γ-gliadin gene on its expression level and gluten strength of wheat. Methods: The prokaryotic expression and reduction–oxidation reactions were performed to identify the effect of TaGli-γ-2.1 on dough strength. Bisulfite analysis and 5-Aza-2′-deoxycytidine treatment were used to verify the regulation of TaGli-γ-2.1 expression by pTaGli-γ-2.1 methylation. The content of gluten proteins composition was measured by RP-HPLC, and the gluten strength was measured by Gluten Index and Farinograph. Results: TaGli-γ-2.1 was classified into a subgroup of γ-gliadin multigene family and was preferentially expressed in the later period of grain filling. Addition of TaGli-γ-2.1 protein fragment into strong gluten wheat flour significantly decreased the stability time. Hypermethylation of three CG loci of pTaGli-γ-2.1 conferred to lower TaGli-γ-2.1 expression. Treatment with 5-Aza-2′-deoxycytidine in seeds of strong gluten wheat varieties increased the expression levels of TaGli-γ-2.1. Furthermore, the accumulations of gliadin and γ-gliadin were significantly decreased in hypermethylated wheat varieties, corresponding with the increasing of gluten index and dough stability time. Conclusion: Epigenetic modification of pTaGli-γ-2.1 affected gluten strength by modulating the proportion of gluten proteins. Hypermethylation of pTaGli-γ-2.1 is a novel genetic resource for enhancing gluten strength in wheat quality breeding.